Analysis of SO2 Emissions and Thermal Anomalies from the Eruption of Mount Lewotobi Laki-laki in November 2024 Using Google Earth Engine - Febryanto Pratama; Lalu Muhamad Jaelani (Institut Teknologi Sepuluh Nopember, 2025)
Mount Lewotobi is one of the active volcanoes located in Wulanggitang District, East Flores Regency, East Nusa Tenggara. Mount Lewotobi Laki-Laki in November 2024 has been detected showing significant volcanic activity. This volcanic activity has been detected emitting volcanic gas emissions and significant lava flows that could affect air quality, structures, and the surrounding ecosystem. SO2 emissions and hotspot areas were analyzed using remote sensing data from Sentinel-5P (TROPOMI), Sentinel-2 (MSI), and Landsat-8 (OLI). Data processing was conducted using the Google Earth Engine platform to obtain spatial and temporal analyses of SO2 concentrations in the air and heat sources generated by volcanic activity. The Normalized Hotspot Indices (NHI) method was applied to identify and map hotspots generated by volcanic activity. The results of SO2 levels showed a maximum value of 300,831 µg/m³ and an average of 71,928 µg/m³ occurring on November 9, 2024. The classification of hotspot distribution indicated a range from high to moderate to low. The total number of hotspots measured was 51 on Landsat-8 and 278 on Sentinel-2. The statistical test results for Landsat-8 data showed no significant correlation between SO2 measurements and hotspot measurements, whereas the results for Sentinel-2 showed an inverse correlation.